Social Media Influencers and Consumer Purchase Intention: A Systematic Review Of Antecedents, Mediators, and Moderators - Muhammad Rezaldi; Daniel Bonartua Malau; Gendhi Haris; Nova Novitasari (CV Putra Publisher, 2026)
This study conducts a focused systematic literature review of 15 empirically rigorous studies published between 2020 and 2025, selected from an initial pool of 65 candidate articles identified through a Scopus database search. Selection prioritized studies that explicitly reported effect sizes, employed structural equation modeling or experimental design, and examined purchase intention as a primary outcome variable. Guided by three research questions, RQ1: what influencer attributes are empirically associated with consumer purchase intention and with what relative strength? RQ2: what psychological mechanisms mediate the relationship between influencer attributes and purchase intention? RQ3: what contextual factors moderate the effectiveness of social media influencers on purchase intention? The review applies the Stimulus-Organism-Response (S-O-R) framework as a unifying theoretical architecture. Trustworthiness emerges as the most consistent predictor (RQ1), information credibility, utilitarian value, and parasocial relationships mediate effects (RQ2), and product category, generational cohort, and influencer type moderate outcomes (RQ3). Research gaps include cross-cultural comparisons, longitudinal designs, and over-endorsement saturation thresholds.